Changes in Occlusal Philosophies for Full Mouth Rehabilitation. Issue 1 (March 2021) - Kelleher, Martin G.D.; Ooi, Hui Lynn; Blum, Igor R.
This article reviews some of the main tenets of different occlusal philosophies involved in 'full mouth rehabilitation' and evolved since the late 19 th century. This review is not intended as a comprehensive historical review of all the people who wrote, researched, or taught on the topic, and it is certainly not intended to disparage their well-meaning contributions. It is intended to highlight some of the changes that occurred in relation to full mouth rehabilitation occlusal concepts along with the dates when they were articulated.